Laboratory supervision of MSc projects: Qualitative interviews, thematic analysis, and recommendations for the supervisor - Astrid Kjær, Helle (Improving University Science Teaching and Learning, 2023)
A range of skills can be obtained by students doing a M.Sc. thesis with a laboratory component. By learning in the practical domain the student can gain a deeper understanding through trial and error. Often the laboratory also include working together with other students, PhD’s, postdocs, laboratory personal and others on joined projects including development of interpersonally skills within team work, negotiation, planning and collaboration. As a supervisor the laboratory M.Sc. thesis offer opportunities to often interact with the students and provide assistance and feedback personalized and in a timely matter (Wakeling, Green, Naiker, & Panther, 2017). However the evaluation of the student experience in the laboratory as part of the M.Sc. thesis is often limited to the exam (written and oral), which is focused on the scientific topic and not on other skills obtained while in the laboratory or during the student learning experience. Here I have made qualitative interviews, based on the questions presented in appendix A, of 5 M.Sc. students from the Ice and Climate group to evaluate their experience doing an M.Sc. with a laboratory component in the interdisciplinary field of ice core science. The interviews were analyzed by common themes. The questions covered prior laboratory experience, experience during the thesis, learning outcomes as experienced by the students as well as questions on how supervisors could improve their supervisions. Through a thematic analysis (Braun & Clarke, 2006) of the student 92 Helle Astrid Kjær responses I suggest how we can improve supervision in the laboratory for coming M.Sc. project students.